Memoranda of agreement and procedures for working on federal lands of the USDA - Nell, L. G., author; Jameson, Donald A., author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1970)
This technical report contains examples of agreements, contracts and procedures and the resulting official paperwork that outlines the cooperation between Colorado State University, the United States Department of Agriculture and individual investigators, as part of the International Biological Program, Grassland Biome studies.
Keywords: U.S. International Biological Program; United States. Department of Agriculture; Colorado State University; United States Department of Agriculture; U.S. International Biological Program; Colorado State University; USDA; agreement; Pawnee National Grasslands; Central Plains Experimental Range